Increasing the Physical Quality of Instant Yogurt by Spray Drying with Instant Additive - Mulyani, S; Indratiningsih, Indratiningsih; Pramono, YB (ANIMAL PRODUCTION, 2004)
This research was carried out to compare the effects of soy lecithin and yolk as instant additive, to know the effects of instant additive level and their interaction on physical quality of instant yogurt (rehydration rate, solubility and viscosity).Â  The data were analyzed by statistical analysis based on Completely Randomized Block Design (CRBD) with factorial pattern (2x3) using one control treatment (without instant additive), if the result were significant, then continued by Duncanâs New Multiple Range test (DMRT).Â  The first factor was variety of instant additive (soy lecithin, yolk), whereas the second factor was concentration of instant additive (0.5, 1.0 and 1.5% v/v).Â  The result of this research showed that variety of instant additive has no significant effect on viscosity, but it has significant effectÂ  (P<0.05) on rehydration rate and solubility.Â  The second factor has significant effect (P<0.05) on solubility, but has no significantly effect on rehydration rate and viscosity.Â  Interaction of them only occurred on solubility of instant yogurt.Â  The result of DMRT showed that the increasing physical quality of instant yogurt occurred on the 0.5% concentration. It was compared with control treatment.Â  Increasing concentration has no effect on rehydration rate, solubility or viscosity, except on solubility.Â  The solubility decreased at level of instant additive 1.5%.Â  The conclusions of this research were soy lecithin and yolk had different ability to increase solubility and rehydration rate but gave similar effect on viscosity.Â  Application of soy lecithin or yolk as instant additive up to 0.5% would increase physical quality of instant yogurt (rehydration rate, viscosity and solubility).Â  As compare to soy lecithin, yolk has better performance in increasing and making stable solubility of instant yogurt. (Animal Production 6(1): 1-8 (2004)Â Key Words:Â  Instant Yogurt, Soy Lecithin, Yolk, Physical Quality